Queer Theories, Critiques and Beyond - Stormhøj, Christel (Kvinder, Køn & Forskning, 2013)
The article examines queer as critique by performing a series of parallel readings of leading queer thinkers, including Judith Butler, Eve Sedgwick, and Michael Warner. Introducing two philosophical traditions and strategies of social critique, immanent and intervening critique, along with their criteria of what is right and good, I discuss how these scholars engage in these strategies and wrestle with their in-built problems within the orbit of the research foci and ambitions of queer studies. Queer critique aims at challenging dominant knowledges, social hierarchies and norms related to sex, sexuality, and gender by exposing the limits they impose on us, including the sufferings associated with them. The article closes with considering queer political visions and their normative underpinnings.